The Impact of Personal Characteristics and Intrinsic Motivation on Creative Behavior among Indonesian Radio Station Managers - Setiadi, Nugroho J.; Ali, Anees Janee; Aafaqi, Rehana (UI Scholars Hub, 2007)
The main purpose of the article is to increase understanding in some personal characteristics affecting creative performance among Indonesian radio station managers’ leadership context. Using creativity-relevant personal characteristics and motivation as input model, the authors identified that both of these two variables are positively related to creative performance. The study hypothesized that Leader-member exchange (LMX) moderate the relationship between personal characteristics and creative performance. Among a sample of 283 Indonesian radio station managers, results found that creativity-relevant personal characteristics and intrinsic motivation were positively related to creative performance when managers’ perception of followers’ work contribution toward them (as the second dimension of LMX) was high.